The Effect of Low Protein Energy-Rich Diets on Plasma Hepatic Markers, Hepatic Damage, and Discrimination Reversal Learning in Young Female Chicks - Bona, Laura; van Staaveren, Nienke; Pokharel, Bishwo Bandhu; van Krimpen, Marinus; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2018)
Consumption of low protein energy-rich (LPER) diets increases susceptibility to metabolic disease in mammals, such as hepatic damage, and can have an adverse effect on cognition. However, the effects of these diets on both physical and mental welfare have not been investigated in domestic meat chickens. Female chicks received a low protein energy-rich or a standard control diet from 21-51 days of age. The effects of these dietary manipulations on plasma hepatic markers for liver damage, liver necropsy, and learning a visual discrimination reversal task were assessed. Birds given access to LPER diets weighed less than chicks that had access to the control diets. All chicks had post-mortem signs of hepatic hemorrhage/increased liver color scores and aspartate aminotransferase (AST) levels above 230U/L indicative of hepatic damage in birds. The LPER diet had no impact on the performance of female chicks when learning to distinguish colors in a reversal visual discrimination task. The present study suggests that liver damage does not become worse when feeding LPER or impact visual reversal learning in female meat-type chickens. However, the high incidence of liver cell damage/liver hemorrhage, and “abnormal” AST activities are of concern in female broiler chicks across both diets, and suggests that the health of modern meat-type genotypes needs to be improved.